Application of the flame hole dynamics to a diffusion flame in channel flow - Lee, SR; Na, Y; Kim, JS (KOREAN SOC MECHANICAL ENGINEERS, 2003)
The method of flame hole dynamics is demonstrated as a mean to simulate turbulent flame extinction. The core of the flame hole dynamics involves derivation of a random walk mapping for the flame holes, created by local quenching, between burning and quenched states provided that the dynamic characteristics of flame edges is known. Then, the random walk mapping is projected to a background turbulent field. The numerical simulations are carried out with further simplifications of flame string and unconditioned scalar dissipation rate. The simulation results show how the chance of partial quenching is influenced by the crossover scalar dissipation rate. Finally, a list of improvements, necessary to achieve more realistic turbulent flame quenching simulation, are discussed.
Keywords: EDGE-FLAMES; PROPAGATION